Gambaran Tingkat Pengetahuan Remaja Putri Tentang Risiko Kehamilan Pada Perkawinan Anak di SMP Negeri 2 Sengkang Kabupaten Wajo - Mayansari Mayansari; Tetti Surianti; Lisna Lisna (Journal Research of Nursing & Midwifery (JRNM), 2025)
Adolescent pregnancy is one of the issues that can lead to high-risk conditions during pregnancy. Adolescent girls’ knowledge about teenage pregnancy is very important in preventing child marriage. This study aimed to describe the level of knowledge of adolescent girls regarding the risks of pregnancy in child marriage at State Junior High School 2 Sengkang, Wajo Regency. This study employed a descriptive research method with a cross-sectional approach. The sample consisted of 168 adolescent girls selected through accidental sampling. Data analysis was conducted by calculating percentages. The results showed that the majority of respondents had a good level of knowledge, with 119 respondents (70.8%), 47 respondents (28%) having sufficient knowledge, and 2 respondents (1.2%) having poor knowledge. Although most adolescent girls demonstrated good knowledge, they still need motivation and support from their surrounding environment. This can help prevent child marriage, which has significant impacts on reproductive health, particularly high-risk pregnancy at a young age. This study recommends the implementation of extracurricular activities focused on preventing child marriage among adolescent girls at State Junior High School 2 Sengkang, Wajo Regency.